2020
DOI: 10.1016/j.brs.2020.02.031
|View full text |Cite
|
Sign up to set email alerts
|

TMS brain mapping of the pharyngeal cortical representation in healthy subjects

Abstract: a b s t r a c tBackground: Brain mapping is fundamental to understanding brain organization and function. However, a major drawback to the traditional Brodmann parcellation technique is the reliance on the use of postmortem specimens. It has therefore historically been difficult to make any comparison regarding functional data from different regions or hemispheres within the same individual. Moreover, this method has been significant limited by subjective boundaries and classification criteria and therefore su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Currently, the intraluminal pharyngeal electromyographic measurements are popularly used to detect the central swallowing excitability due to the potential reliability [7]. A recent study reported that eliciting pharyngeal MEPs is more difficult than those of other muscles [8]. Our pilot study, however, suggested that sEMG recordings of lip OO muscle activities through fMRI-guided nTMS could aid in the detection of the SMC muscles' MEPs for localization of the SMC target in M1.…”
Section: Dear Editormentioning
confidence: 82%
“…Currently, the intraluminal pharyngeal electromyographic measurements are popularly used to detect the central swallowing excitability due to the potential reliability [7]. A recent study reported that eliciting pharyngeal MEPs is more difficult than those of other muscles [8]. Our pilot study, however, suggested that sEMG recordings of lip OO muscle activities through fMRI-guided nTMS could aid in the detection of the SMC muscles' MEPs for localization of the SMC target in M1.…”
Section: Dear Editormentioning
confidence: 82%
“…Bilateral TMS stimulation of the motor cortex has been found to induce UES MEP ( Ertekin et al, 2001 ), and the demonstration of volitional control of UES relaxation with high-resolution manometry biofeedback ( Nativ‐Zeltzer et al, 2019 ) indicated cortical involvement in the regulation of the UES relaxation. Neuroanatomically, the corticobulbar tract originating from the lateral aspect of the primary motor cortex ( Hamdy, 2006 ) is located within the precentral gyrus, and the cricopharyngeus muscles receive fibers from both sides ( Li et al, 2020 , Aziz et al, 1996 ). Our findings on the correlation of UOD with the FC between the bilateral precentral gyrus and the medulla may be related to the role of the precentral gyrus in hyoid movement or to direct regulation of the relaxation aspect of the UES opening.…”
Section: Discussionmentioning
confidence: 99%
“…The swallowing process remains controversial in terms of the degree of lateralization. Several studies have shown that swallowing exhibits asymmetries in the cerebral hemispheres ( 20 , 21 ). Studies have shown differences in swallowing physiology between right- and left-sided unilateral stroke patients, with pharyngeal damage being more severe in patients with right-hemisphere strokes ( 22 ).…”
Section: Discussionmentioning
confidence: 99%